2018
DOI: 10.2147/ott.s156844
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter hepatic arterial infusion chemotherapy vs sorafenib in the treatment of patients with hepatocellular carcinoma of Barcelona Clinic Liver Cancer stage C: a meta-analysis of Asian population

Abstract: ObjectiveTo compare the clinical efficacy and safety of transcatheter hepatic arterial infusion chemotherapy (HAIC) with those of sorafenib in the treatment of patients with hepatocellular carcinoma (HCC) of Barcelona Clinic Liver Cancer (BCLC) stage C.MethodsPotentially relevant studies comparing the clinical efficacy and safety of HAIC with those of sorafenib were searched using Medline, PubMed, Embase, Cochrane Library, and Chinese databases (Wanfang Data and China National Knowledge Infrastructure). Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Through systematic literature retrieval, a total of 5 articles were included in this study. Different from the conclusion of previous systematic reviews [27][28][29], the study showed that sorafenib could prolong the overall survival of patients with TACE-refractory HCC compared with HAIC (HR = 1.69, 95% CI [1.09, 2.62], p=0.018). Although the ORR of the HAIC group was significantly higher than that of the sorafenib group (RR = 3.08, 95%CI [1.38, 6.87], p=0.006), the DCR between the HAIC group and the sorafenib group was not significantly different (RR = 0.94, 95%CI [0.60, 1.48], p=0.798).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Through systematic literature retrieval, a total of 5 articles were included in this study. Different from the conclusion of previous systematic reviews [27][28][29], the study showed that sorafenib could prolong the overall survival of patients with TACE-refractory HCC compared with HAIC (HR = 1.69, 95% CI [1.09, 2.62], p=0.018). Although the ORR of the HAIC group was significantly higher than that of the sorafenib group (RR = 3.08, 95%CI [1.38, 6.87], p=0.006), the DCR between the HAIC group and the sorafenib group was not significantly different (RR = 0.94, 95%CI [0.60, 1.48], p=0.798).…”
Section: Discussioncontrasting
confidence: 97%
“…Compared with sorafenib, HAIC shows a better therapeutic effect and a lower incidence of adverse events (AEs) in the treatment of advanced or unresectable HCC [27][28][29]. HAIC has been widely used in Japan [12].…”
Section: Discussionmentioning
confidence: 99%
“…Zhuang BW et al [24] which conducted a meta-analysis about the safety and benefits of sorafenib versus HAIC for advanced HCC, found that HAIC found that HAIC was more effective and safe than sorafenib and recommend HAIC as an alternative treatment for advanced HCC. Another meta-analysis implemented by Ni JY et al [39], compared the HAIC versus sorafenib for HCC patients with BCLC stage C; they also reported that HAIC achieved better tumor response and clinical efficacy and recommend HAIC for patients with HCC of BCLC stage C. The two previous studies were all compared HAIC with sorafenib for advanced patients(BCLC stage C). BCLC stage C was mean with vascular invasion, extrahepatic spread, Child-Pugh A or B, Performance status (PS) 1 or 2 and was defined as advanced stage disease [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of sorafenib can be compromised (1)(2)(3)(4); it has been shown to significantly extend the median survival time of treated patients, but only by 3-5 months. This has largely been attributed to the development of resistance within 6 months (3)(4)(5)(6). Combination of sorafenib and cytotoxic chemotherapeutic agents, or molecular targeted agents, or immunotherapeutic drugs were studied to overcome sorafenib resistance in HCC (7).…”
Section: Introductionmentioning
confidence: 99%